Bordering encounters, sociality and distribution of the ability to live a ‘normal life’ - Dzenovska, D (Wiley, 2014)
Based on analysis of a bordering encounter that took place in the offices of the Latvian State Border Guard, I trace how bordering produces connections at the same time as it effects separations. Despite being separated by state-based lines of power, participants of the bordering encounter - all former Soviet citizens - recognised each other as 'normal people' striving to obtain a 'normal life'. This connection was enabled by historically formed understanding of shared conditions of life and critical awareness of global power hierarchies. The sociality formed during the bordering encounter invites a rethinking of how distribution of life is negotiated through bordering, and how politics is imagined in relation to borders.